Principles of heat transfer - Kreith, Frank; Manglik, Raj M. (Cengage Learning, 2018)
Now you can learn the principles of heat transfer using the classic that sets the standard of coverage and organization for all other heat transfer texts. Following the recommendations of the ASME Committee on Heat Transfer Education, Kreith/Manglik's PRINCIPLES OF HEAT TRANSFER, 8E provides a comprehensive engineering approach that is ideal for your study of heat transfer. This relevant book recognizes that in today's world, computational analysis is more critical than rote mathematical solutions to heat transfer problems. However, the authors also incorporate an effective analytic approach that offers a clear understanding of the physics involved and equips you with the tools for analyzing more complex problems. The book emphasizes applications to current engineering challenges in renewable energy, bioengineering, microelectronics, materials processing, and space exploration to arm you with the practical knowledge you need for success.